2010
DOI: 10.1002/lt.21967
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma and reality of transplant tourism: An ethical perspective for liver transplant programs

Abstract: Transplant programs are likely to encounter increasing numbers of patients who return after receiving an organ transplant abroad. These patients will require ongoing medical care to monitor their immunosuppression and to provide treatment when the need arises. Transplant societies have condemned transplantation with organs purchased abroad and with organs procured from executed prisoners in China. Nevertheless, transplant programs require guidance on how to respond to the needs of returning transplant tourists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…However, the majority of existing reports are in the form of news media (Economist, 2008;James, 2009), commentaries or editorials (Budiani-Saberi & Delmonico, 2008;Delmonico, 2009;Jacek, 2012), perspectives, briefs, or conceptual papers (Caballero-Danell & Mugomba, 2007;Heung, Kucukusta, & Song, 2010;Smith & Forgione, 2007), reviews (Behrmann & Smith, 2010;Caballero-Danell & Mugomba, 2007;Carrera & Bridges, 2006;Crooks et al, 2010;George, Henthorne, & Williams, 2010;Heung et al, 2010;Lunt & Carrera, 2010;Lunt et al, , 2012Pennings et al, 2009), and case studies (Kangas, 2010;Moghimehfar & Nasr-Esfahani, 2011;NaRanong & NaRanong, 2011;Schiano & Rhodes, 2010). Relatively few empirical studies have been reported (Blyth, 2010;Canales, Kasiske, & Rosenberg, 2006;Karuppan & Karuppan, 2010Pennings et al, 2009;Satjapot, Johnson, & Garman, 2011;Shenfield et al, 2010;Tsai et al, 2011).…”
mentioning
confidence: 97%
“…However, the majority of existing reports are in the form of news media (Economist, 2008;James, 2009), commentaries or editorials (Budiani-Saberi & Delmonico, 2008;Delmonico, 2009;Jacek, 2012), perspectives, briefs, or conceptual papers (Caballero-Danell & Mugomba, 2007;Heung, Kucukusta, & Song, 2010;Smith & Forgione, 2007), reviews (Behrmann & Smith, 2010;Caballero-Danell & Mugomba, 2007;Carrera & Bridges, 2006;Crooks et al, 2010;George, Henthorne, & Williams, 2010;Heung et al, 2010;Lunt & Carrera, 2010;Lunt et al, , 2012Pennings et al, 2009), and case studies (Kangas, 2010;Moghimehfar & Nasr-Esfahani, 2011;NaRanong & NaRanong, 2011;Schiano & Rhodes, 2010). Relatively few empirical studies have been reported (Blyth, 2010;Canales, Kasiske, & Rosenberg, 2006;Karuppan & Karuppan, 2010Pennings et al, 2009;Satjapot, Johnson, & Garman, 2011;Shenfield et al, 2010;Tsai et al, 2011).…”
mentioning
confidence: 97%
“…Routinizing and normalizing opioid use queries would help physicians execute their duty to approach patients who do have an opioid use history with nonjudgmental regard. 4 Surgeons' Roles First, physicians have a duty to learn about a patient's medical history and apply what's relevant in it to that patient's present clinical situation. A surgeon planning an intervention must understand and consider any medical therapy that could influence potential risks and benefits.…”
Section: Commentarymentioning
confidence: 99%
“…Rhodes et al [12] discussed two cases that raised this dilemma, and argued for upholding commitments to traditional principles of beneficence and non-judgmental regard in sorting out the policies that a transplant centre should adopt. Adopting positions based solely on high moral grounds without consideration of the plight of the affected patients might not be appropriate [65] . Most professional societies do not condone TT but this should not abrogate a physician's right to care for such patients.…”
Section: Effect Of Tt On Transplant Servicesmentioning
confidence: 99%